2010
DOI: 10.1007/s12098-010-0118-x
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic colonization of upper respiratory tract by potential bacterial pathogens

Abstract: S. pneumoniae carriage rate was comparatively higher in the Community and its antimicrobial resistance is an issue to address.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
11
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 9 publications
3
11
1
Order By: Relevance
“…The high resistance (25.5 %) of GAS to tetracycline reported here is comparable to the global rise noticed (Aggarwal et al, 1984;Dhakal et al, 2010;Jain et al, 2008;Lloyd et al, 2007;Ray et al, 2010;Smeesters et al, 2010;Traub & Leonhard, 1997;Zaoutis et al, 1999) that has been assigned to polyclonal dissemination of resistance types, as antibiotic resistance encoded by transposable elements does occur in GAS. GAS resistance (3.9 %) to chloramphenicol and susceptibility to vancomycin reported in this study are similar to results from previous reports (Jain et al, 2008).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The high resistance (25.5 %) of GAS to tetracycline reported here is comparable to the global rise noticed (Aggarwal et al, 1984;Dhakal et al, 2010;Jain et al, 2008;Lloyd et al, 2007;Ray et al, 2010;Smeesters et al, 2010;Traub & Leonhard, 1997;Zaoutis et al, 1999) that has been assigned to polyclonal dissemination of resistance types, as antibiotic resistance encoded by transposable elements does occur in GAS. GAS resistance (3.9 %) to chloramphenicol and susceptibility to vancomycin reported in this study are similar to results from previous reports (Jain et al, 2008).…”
Section: Discussionsupporting
confidence: 84%
“…Worldwide data suggest an increased resistance of GAS to macrolides, ranging from 0. A Cd E At Cw T C Nv Ak G Throat isolates 11 + 2 2 2 2 2 + 2 2 2 57 2 2 2 + + + 2 2 2 2 85 2 + + 2 2 2 2 2 2 2 Skin isolates 12 2 2 2 2 + 2 + + 2 2 22.8 2 2 2 + 2 2 + 2 2 2 44 2 2 2 + 2 2 2 + 2 2 44 + 2 2 + 2 + 2 2 2 2 44 2 2 + 2 2 2 2 + 2 2 44 2 2 2 + 2 2 2 + 2 2 44 2 2 2 + + + 2 + 2 2 44 2 2 2 2 2 2 2 2 2 2 49 2 2 2 + + + 2 2 2 2 75.1 2 2 2 2 2 + 2 + 2 2 81 2 2 + 2 2 2 2 2 + 2 81 2 2 2 2 2 + 2 + 2 + 85 2 2 2 2 2 + 2 + 2 2 RF isolates 11 2 2 2 2 2 + 2 + 2 2 67 2 2 2 2 2 + 2 + 2 2 Invasive disease isolates 58 2 2 2 2 2 + + 2 2 2 87 2 2 + 2 2 + 2 2 + 2 95 2 2 2 2 2 + 2 + + 2 Rowe et al, 2009;Traub & Leonhard, 1997); a review of Indian literature showed a gradual increase upto 29.4 % up until 2010 (Brahmadathan et al, 2005;Capoor et al, 2006;Dhakal et al, 2010;Lloyd et al, 2007;Mathur et al, 2002). The absence of, or very low, erythromycin resistance among GAS from pharyngitis and RF patients in the present study is quite similar to previous findings (Brahmadathan et al, 2005;Rijal et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, only 3.5% of GAS isolates were resistant to tetracycline in Spain (23). However, the current study result was in agreement with the reports on global rise of tetracycline-resistant GAS (26,27). With regard to the resistance gene, the presence of mefA in an erythromycin-susceptible isolate in the current study is not surprising.…”
Section: Discussionsupporting
confidence: 91%
“…One hundred and sixty isolates were found to be β-hemolytic (15.28%) and out of these, 92 isolates were identified as GAS. We found a high prevalence of GAS (8.79%) as compared to the previous studies from different regions of India (3% and 2.8% in the northern part and 4.5% in the southern part) [10,17,30]. A potential reason for the discordant data may be explained by our selection of clinical samples collected from patients with symptoms suggestive of GAS infection.…”
Section: Discussioncontrasting
confidence: 59%